A novel approach to periodic event-triggered control: Design and application to the inverted pendulum. (November 2016) - Aranda-Escolástico, Ernesto; Guinaldo, María; Gordillo, Francisco; Dormido, Sebastián
Abstract: In this paper, periodic event-triggered controllers are proposed for the rotary inverted pendulum. The control strategy is divided in two steps: swing-up and stabilization. In both cases, the system is sampled periodically but the control actions are only computed at certain instances of time (based on events), which are a subset of the sampling times. For the stabilization control, the asymptotic stability is guaranteed applying the Lyapunov–Razumikhin theorem for systems with delays. This result is applicable to general linear systems and not only to the inverted pendulum. For the swing-up control, a trigger function is provided from the derivative of the Lyapunov function for the swing-up control law. Experimental results show a significant improvement with respect to periodic control in the number of control actions. Abstract : Highlights: A periodic event-triggered control strategy for general linear systems. The strategy is applied to the stabilization of the rotary inverted pendulum. A periodic event-triggered control strategy for the swing-up of the inverted pendulum. Theoretical criteria to determine the sampling period and triggering parameters. Experimental results on a real plant show the efficiency of the scheme.